The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1186/1475-2875-10-187
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum isolates from southern Ghana exhibit polymorphisms in the SERCA-type PfATPase6 though sensitive to artesunate in vitro

Abstract: BackgroundIn 2005, Ghana replaced chloroquine with artemisinin-based combination therapy as the first-line treatment for uncomplicated malaria. The aim of this work was to determine for the first time, polymorphisms in the putative pfATPase6 and pftctp, pfmdr1, pfcrt genes in Ghanaian isolates, particularly at a time when there is no report on artemisinin resistance in malaria parasites from Ghana. The sensitivity of parasite isolates to anti-malaria drugs were also evaluated for a possible association with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
1
25
2
1
Order By: Relevance
“…The four important SNPs in Pfatpase6 gene reported to be associated with artemisinin resistance in different studies are L263E, E431K, A623E, and S769N (Tahar et al 2009;Jambou et al 2010;Krishna et al 2010;Zakeri et al 2012). However, L263E was not observed in any of the field isolates in all the studies conducted so far (Kwansa-Bentum et al 2011;Tanabe et al 2011) but only detected in vitro (Uhlemann et al 2005). The studies on P. falciparum isolates from Suriname too revealed L263, A623, and S769 codons in Pfatpase6 gene to be wild type (Adhin et al 2012).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The four important SNPs in Pfatpase6 gene reported to be associated with artemisinin resistance in different studies are L263E, E431K, A623E, and S769N (Tahar et al 2009;Jambou et al 2010;Krishna et al 2010;Zakeri et al 2012). However, L263E was not observed in any of the field isolates in all the studies conducted so far (Kwansa-Bentum et al 2011;Tanabe et al 2011) but only detected in vitro (Uhlemann et al 2005). The studies on P. falciparum isolates from Suriname too revealed L263, A623, and S769 codons in Pfatpase6 gene to be wild type (Adhin et al 2012).…”
Section: Discussionmentioning
confidence: 73%
“…Also, in Southern-Iran, L263 and A623 were reported to be wild type (Zakeri et al 2012). The presence of S769N also made occasional impacts from few studies (Jambou et al 2005;Pillai et al 2012;Zakeri et al 2012) like that of the French Guiana (Legrand et al 2008) while there are reports which observed its absence in the P. falciparum isolates that were analyzed (Mugittu et al 2006;Sisowath et al 2007;Zhang et al 2008;Ferreira et al 2008;Menegon et al 2009;Wangai et al 2011;Kwansa-Bentum et al 2011;Tanabe et al 2011;Brasil et al 2012;Saha et al 2013) or even denied the association of this SNP with artemisinin resistance (Phompradit et al 2011;Cui et al 2012). Another study from Yaounde, Cameroon, where all these four mutations were tested, high prevalence of E431K was warranted and alarmed (Tahar et al 2009).…”
Section: Discussionmentioning
confidence: 90%
“…The 68 pfatp6 sequences recently obtained in southern Ghanaian samples were partial sequences and were excluded in our analysis [54]. Comparison of all pfatp6 sequences identified a total of 71 SNPs, including 30 synonymous and 41 non-synonymous.…”
Section: Resultsmentioning
confidence: 99%
“…Concerns about artemisinin resistance have been reported recently [22], and all malaria-endemic countries have been warned to be more vigilant in monitoring antimalarial drug efficacy, to allow the early detection of artemisinin resistance and aid global malaria control [23][24][25]. Furthermore, most rapid diagnostic test kits currently available on the market are based on HRPII and pLDH (as a biomolecule).…”
Section: Discussionmentioning
confidence: 99%